The transforming growth factor-βs: structure, signaling, and roles in nervous system development and functions - Böttner, Martina; Krieglstein, Kerstin; Unsicker, Klaus (Journal of neurochemistry, 2000)
Abstract: Transforming growth factor-βs (TGF-βs) are amongthe most widespread and versatile cytokines. Here, we first provide a briefoverview of their molecular biology, biochemistry, and signaling. We thenreview distribution and functions of the three mammalian TGF-β isoforms,β1, β2, and β3, and their receptors in the developing and adultnervous system. Roles of TGF-βs in the regulation of radial glia,astroglia, oligodendroglia, and microglia are addressed. Finally, we reviewthe current state of knowledge concerning the roles of TGF-βs incontrolling neuronal performances, including the regulation of proliferationof neuronal precursors, survival/death decisions, and neuronaldifferentiation.